Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-04-01T17:22:04+02:00
Développements:

A= 4(5x -3) - (2x -1) (x +4)
A= 20x -12 - (2x² +8x -x -4)
A= 20x -12 -2x² -7x +4
A= -2x² +13x -8

B= (7x -2)²
B= (7x -2) (7x -2)
B= 49x² - 14x -14x +4
B= 49x² -28x +4

C= (3x +5y) (3x -5y)
C= 9x² -15xy +15xy -25y²
C= 9x² - 25y²

Voilà ! J'espère t'avoir aidé(e) ! :)
2014-04-01T17:26:16+02:00
Développer les expressions :

A = 4(5x - 3) - (2x - 1) (x + 4)
A = 20x - 12 - (2x² + 7x - 4)
A = -2x² + 13x - 8

B = (7x - 2)²
B = (7x - 2) (7x - 2)
B = 49x + 49x - 14x - 14x + 4
B = 49x² - 28x + 4

C = (3x + 5y) (3x - 5y)

C = 9x  + 9x - 15xy -25y - 25y + 15xy
C = 9x² - 25y²


Le C n'est pas logique car 9x + 9x = 18x et il est écrit 9x^2 , de même pour -25y ...